Spin-current in a Magnetic Semiconductor Tunnel Junction: Effect of External Bias Voltage - Nguyen, Thi Loan; Drouhin, Henri-Jean; hoai, nguyen (Communications in Physics, 2022)
This paper investigates spin-current transport in a GaMnAs/GaAs/GaMnAs magnetic semiconductor tunnel junctions under applied bias voltages. The 30-band k.p approach is used to describe the materials within the heterostructure, incorporating both spin-orbit and exchange interactions. We use the transfer-matrix formalism to derive numerical solutions for the wave functions. At specific bias values, we calculate the polarization of the spin-current component along the z direction of the structure. We show oscillations of the two spin-current components perpendicular to the magnetization with equal polarization amplitude and characteristic period. The polarization amplitude varies around 10%, reflecting the typical polarization in such type of material. The oscillation period - which relates to the Larmor frequency for spin precession - increases with the bias voltage values.